Association between serum 25-hydroxyvitamin D and osteoarthritis: A national population-based analysis of NHANES 2001–2018 - Yu, Guoyu; Lin, Yuan; Dai, Hanhao; Xu, Jie; Liu, Jun (Frontiers in Nutrition, 2023)
Background: Previous studies have not provided a consensus on the effect of serum 25-hydroxyvitamin D [25(OH)D] on osteoarthritis(OA). We aimed to evaluate the association using a large, nationally representative sample. Methods: The cross-sectional data were obtained from the 2001–2018 National Health and Nutrition Examination Survey (NHANES). Individuals aged≥40 years who had information of serum 25(OH)D, self-report OA, and related covariates were included. Multivariable logistic regression analysis was employed to assess the association between serum 25(OH)D and osteoarthritis. Results: Among the 21,334 participants included (weighted mean age, 56.85 years; 48.49% men), the proportion of participants with high serum 25(OH)D concentrations (≥100 nmol/L) increased significantly from 4.22% in 2001-2006 to 18.77% in 2013-2018. Higher serum 25(OH)D levels were associated with more osteoarthritis prevalence in fully adjusted model (odd ratio [OR] 1.25[95% CI: 1.10,1.43] for the 50–75 nmol/L group; OR 1.62[ 95% CI: 1.42,1.85] for the 75-100 nmol/L group; OR 1.91[ 95% CI: 1.59,2.30] for the ≥100 nmol/L group; with <50 nmol/L group as the reference) (P<0.001 for trend). The association was consistent in sensitivity analyses by propensity score-adjusted regression or excluding participants who had received vitamin D supplement. In subgroup analysis, the OR for the association increased significantly with body mass index (BMI) (BMI<25 kg/m2,1.01[95% CI: 1.04,1.08]; BMI 25-30 kg/m2,1.05[95% CI: 1.01,1.08]; BMI≥ 30 kg/m2,1.10[95% CI: 1.06,1.13]; p=0.004 for interaction). Conclusion:There was a positive correlation between serum 25(OH)D and osteoarthritis with a possible modification by BMI. Our finding raises concerns about the potential adverse effects of high serum 25(OH)D on osteoarthritis, particularly among obese individuals. More well-designed studies are still needed to validate our findings in future.